Preparation and characterization of nanocomposites of natural rubber with polystyrene and styrene-methacrylic acid copolymer nanoparticles - T. Nuruk; C. Suksawad; A. Chaiyasat; P. Chaiyasat (eXPRESS Polymer Letters, 2012)
Composites of natural rubber (NR)/vinyl polymer nanoparticles as polystyrene (PS) and poly(styrenemethacrylic acid) (P(S-MAA)) were prepared by heterocoagulation technique. The polymer nanoparticles were prepared by emulsifier-free emulsion polymerizations at 70°C using potassium persulfate as initiator. Under acidic condition where positive charge was present on the NR latex (NRL) surface, the nanoparticles having negative charge mainly from sulfate group of initiator were able to adsorb on the NRL surface, the electrostatic interaction being the driving force. The scanning electron micrographs showed that the polymer nanoparticles are homogenously distributed throughout NR matrix as nanoclusters with an average size of about 500 and 200 nm for PS and P(S-MAA), respectively. The mechanical properties of NR/PS and NR/P(S-MAA) composite films were compared with the NR host. The nanocomposites, particularly when the polymer nanoparticles are uniformly dispersed, possess significantly enhanced mechanical properties strongly depending on the morphology of the nanocomposites.